Impact Of Agroforestry Practices On The Socio-Economy And Environment Of Vientiane Province, Lao Pdr - Ninchaleune, Bounheuang (2007)

(untitled)
In Lao PDR, deforestation is mainly caused by inappropriate logging, and shifting cultivation. These unsustainable agricultural practices and forest utilization have resulted serious natural catastrophe in many parts of the country. The poverty of the three main ethnic groups namely: Lao Loum (lowlander), Lao Theung (uplander) and Lao Soung (highlander) in the rural areas is directly related to land degradation, limitation of agricultural land and absence of alternative source for cash income. In addition, due to high population growth, this people have encroached into the natural forests to produce the food security. For example, they cleared the forest land areas for practising of shifting cultivation. They also legally and illegally harvested the timber forest products (TFPs), collected the non-timber forest product (NTFPs) and hunted wildlife to generate family income, especially during the rice shortage.In Vientiane Province, the hill tribes live closer to lowlander through resettlement and land and forest allocation programs of Lao Government. Based on this condition, Vientiane Province is suitable and meaningful for this study. Nine villages were selected to represent the three main ethnic groups. The three main ethnic groups practice different agricultural practices, and utilize the forest products. The accessibility to the study site is possible through all-weather-road. The general objectives of this study are to assess the impact of agroforestry practices on socio-economic and environmental of Vientiane Province, Lao PDR. The collection of socio-economic data applied the technique of Rapid Rural Appraisal/Participatory (RRA/PRA). Additionally, the Braun-Blanquet method was used for collecting of vegetation data. The main findings of this study are summarized as follows: There were differences in paddy rice cultivation, home garden, tree planting, and livestock raising among these three main ethnic groups. The production of upland rice, bananas, papaya, maize, and showed no differences. This indicates that three main ethnic groups had similarly agricultural production. The change in agricultural practices among three main ethnic groups was dependent on the Lao Government Policies. The study also found that most of Lao Theung and Lao Soung (hill tribes) preferred practicing paddy rice cultivation. However, they still lacked capital and labour in changing their shifting cultivations to paddy rice cultivation. The paddy rice, home garden, agroforestry, and fish pond are considered as good agricultural practices. The result showed that these required relatively smaller size compared to unsustainable practices like shifting cultivation, maize, and grazing land, which are considered to have negative effects to the environment. The forest utilization in terms of quantity among the three main ethnic groups was difference of timber exploitation, and collecting of NTFPs. As a result, Lao Soung and Lao Theung harvested more TFPs than Lao Loum. However, utilization of bamboo, firewood, and hunting were not different. These indicate that all three main ethnic groups utilized the NTFPs. In the 1-, 5-, and 15-year-old fallows, logged-over and primary forests, 170, 209, 227, 236 and 237 individual species were identified, respectively. These five vegetation types comprised of 1097 species with 909 genera and 376 families. Forty-five of relevés could be differentiated in twelve plant communities. The natural recovery had a greater similarity to primary forests, particularly to logged-over forests with similarity value of 0.429 (42.29%). However, 15-, 5- and 1-year-old fallows have similarity value of 0.399 (39.90%), 0.348 (34.80%), and 0.261 (26.10%), respectively. This indicates that three fallow types have been heavily degraded, and requires long time for its natural recovery. The result of regression analysis shows that the farmer’s income from agro and non-agroforestry activities was affected by AG, EDU, FS, HLB, LS and LEX. The AG, EDU, and LS had relationship with income. However, there were not statistically significant. The FS, HLB, LEX, AGROD, LLD, LTD and LSD had relationship with farmer’s income in both models, which had positively expected sign. Therefore, government should consider these factors such as FS, HLB, LEX, AGROD LLD, LTD and LSD when implementing an agroforestry project to increase farmer’s income. The result of the regression analysis of farmer’s agricultural production function shows that the farmer’s agricultural production function was affected by LAB, CAP, LLD, LTD and LSD. This function also had relationship with LAB, CAP LLD, LTD and LSD in both models, which possessed positively expected sign. Based on this result, the Lao Government should consider LAB, CAP, LLD, LTD and LSD when increasing the agricultural production in this study area. In conclusion, all farmers are in need of financial and technical support to practice permanent agriculture. In responding to this need, Lao government should encourage them by providing financial and technical support. In addition, degraded forestland should be rehabilitated with commercial tree and NTFPs species through technical support of the local authorities.